2021
DOI: 10.3390/su13052902
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Predictors of Resilience and Work Engagement during the COVID-19 Pandemic

Abstract: Previous studies have acknowledged the importance of resilience in enabling individuals to cope and bounce back from crises and unexpected situations like the COVID-19 pandemic. Thus, this study advances conservation of resources theory by investigating the job, social, and personal resources underlying employees’ resilience, and the impact of resilience in stimulating job engagement amid the COVID-19 pandemic. The model was tested using data collected from 259 employees in Malaysia. Results of path modeling a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
128
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(176 citation statements)
references
References 94 publications
(130 reference statements)
13
128
0
2
Order By: Relevance
“…A study conducted on a sample of Malaysian employees showed that resilience was significantly associated with work engagement. Furthermore, self-efficacy influenced work engagement directly and indirectly through resilience [ 55 ]. A research carried out on a sample of Vietnamese tourism employees highlighted that core beliefs challenge was positively related to workers’ resilience while cognitive reappraisal played a mediating role in this relationship [ 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…A study conducted on a sample of Malaysian employees showed that resilience was significantly associated with work engagement. Furthermore, self-efficacy influenced work engagement directly and indirectly through resilience [ 55 ]. A research carried out on a sample of Vietnamese tourism employees highlighted that core beliefs challenge was positively related to workers’ resilience while cognitive reappraisal played a mediating role in this relationship [ 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…Applying the CoR theory to the current pandemic, Ojo et al ( 2020 ) found that individual reaction and subsequent response to the crisis varies. Some people can bounce back easily and shortly (Luthans et al, 2006 ; Malik and Garg, 2020 ) while some people will develop the symptoms such as depression or other psychiatric disorders.…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…For many of them, mandatory mass teleworking has blurred boundaries between their personal and work life (Ru-dolph et al, 2020). Some employees had to contend with pay cuts, unpaid leave or job loss (Ojo et al, 2021), which increased uncertainty vis-à-vis job and financial security (Britt et al, 2020;Rudolph et al, 2020). Employees likewise faced challenges in the way their work was organized, that is, they experienced elevated workload (e.g., Wang et al, 2021) and unclear job instructions (i.e., high role ambiguity; Rigotti et al, 2021;Rudolph et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Although studies have begun to identify the individual and organizational factors that support employees to adopt resilient responses during the COVID-19 crisis (e.g., Heath et al, 2020;Kuntz, 2021;Ojo et al, 2021), much research is needed to identify resilience-promoting factors that may diminish the negative impact of stressors and help to build a resilience capacity. For example, in her qualitative study, Kuntz (2021) highlighted both individual factors (e.g., personality traits and personal resources such as self-efficacy) and organizational-level factors (e.g., managerial support, role clarity, supportive communication, ongoing feedback) that help em-ployees to deal with the pandemic-related job stressors (e.g., work overload, job complexity) and to maintain their psychological well-being during COVID-19.…”
Section: Introductionmentioning
confidence: 99%